INQUIRY-BASED SCIENCE COMIC PHYSICS SERIES INTEGRATED WITH CHARACTER EDUCATION - Yulianti, D; Khanafiyah, S; Sulistyorini, S (Jurnal Pendidikan IPA Indonesia, 2016)
This study aimed to test the level of readability and feasibility of science comic, to knowcharacter development through a small test in some schools. The research design was Research & Development, trials were using quasi-experimental pre-test-post-test experimental design. The instruments to measure attitudes were: a questionnaire and observation sheet, a test used to measure comprehension of the material. The results showed that learning science by inquiry-based science comic can improvecharacters and cognitive achievement of primary school students. Results in the form of inquiry-based science comic can be utilized in learning science as a companion teaching materials.